N-doped porous carbon derived from macadamia nut shell for CO2 adsorption - Bai, Jiali; Huang, Jiamei; Yu, Qiyun; Demir, Muslum; Kilic, Murat; Altay, Bilge Nazli; Hu, Xin; Wang, Linlin (Fuel processing technology, 2023)
Selective adsorption and converting CO2 upon efficient solid-based adsorbents is critical for net-zero accomplishment. Herein, we develop an advisable strategy to prepare nitrogen-enriched porous carbons using the macadamia nutshell (MNS) as a carbon precursor, KOH as the activator and melamine as the nitrogen agent, respectively. The as-prepared porous carbons exhibit an enhanced specific surface area of 1731 m2/g and high microporosity with abundant nitrogen functional groups and structural defects. The CO2 uptake of 6.61 and 4.35 mmol g−1 were achieved at 0 and 25 °C, respectively, under 1 bar. More importantly, these biomass-based nitrogen-doped carbons possess various CO2 adsorption merits such as quick adsorption kinetics, high CO2/N2 selectivity, medium heat of adsorption, outstanding uninterrupted recyclability and good dynamic CO2 capture capacity. The present study provides an advanced protocol to design nitrogen-doped porous Carbon via a facile route toward the capture of CO2, which offers excellent progress in sustainable chemistry and engineering. [Display omitted] •N-doped porous carbons were synthesized from biomass waste.•Macadamia nut shell as the precursor, melamine as the N source, KOH as the activator.•The obtained carbon exhibits high CO2 adsorption capacity, 6.61 mmol g−1 at 0 °C and 1 bar.•The adsorbents also possess many good CO2 adsorption properties.•Synergetic effect of narrow microporosity and N functionalities determines CO2 uptake.